2011
DOI: 10.3846/13923730.2011.604537
|View full text |Cite
|
Sign up to set email alerts
|

Construction Project Cash Flow Planning Using the Pareto Optimality Efficiency Network Model / Statybos Projekto Pinigų Srautų Planavimas, Naudojant Pareto Optimumo Efektyvumo Tinklo Modelį

Abstract: Cash flow is crucial for ensuring the viability of a project. It consists of a complete history of all cash disbursement, cash shortage, loans, cost of money, and all earnings received. Although significant research work has been conducted on cash flow forecast, planning, and management, the objective is constantly the maximization of profit/final cash balance, or minimization of total project cost. Moreover, cash flow forecasting needs to be effective and fast. The paper develops multiple-objective cash flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The construction industry is a sector having significant uncertainties (Jiang et al 2011). Many authors listed cost overrun and delay are the major uncertainties in construction projects (Abdul-Rahman et al 2011;Lin et al 2011).…”
Section: Cost Prediction Techniquesmentioning
confidence: 99%
“…The construction industry is a sector having significant uncertainties (Jiang et al 2011). Many authors listed cost overrun and delay are the major uncertainties in construction projects (Abdul-Rahman et al 2011;Lin et al 2011).…”
Section: Cost Prediction Techniquesmentioning
confidence: 99%
“…Akbiyikli (2013) analysed financial aspects of road projects and concluded, that investments, project duration and maintenance costs are the most important factors. Jiang et al (2011) developed multiple-objective cash flow planning model -Pareto optimality efficiency network model, which considers typical banking instruments, the constraints of the financial market, the budget constraints, and retention of money. Ashuri et al (2012) concluded that the net present value (NPV) approach is insufficient to measure the economic risk of BuildOwn-Transfer (BOT) road construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…Similar problems were also considered by Zavadskas et al (2010b), Medineckiene et al (2011, Burduk andChlebus (2009), Nowakowski (2010), Zhang and Gao (2010), Wang (2011, 2012) and Chen et al (2012). Pareto-optimal method was proposed by Jiang et al (2011) for the construction project cash flow planning. The review of the modern approaches in this field can be found in the work of Sarker et al (2012).…”
Section: Introductionmentioning
confidence: 92%